Tasawuf sebagai Jembatan Rasionalitas dan Spiritualitas: Kajian Pemikiran Al-Ghazali dalam Konteks Islam Klasik - Muhdi Ali; Masbuang; Suadi Sa’ad; Endang Saeful Anwar (STAIN MAJENE, 2025)
The debate on the relationship between rationality and spirituality has been a central theme in classical Islamic thought. Al-Ghazali (d. 1111 CE) occupies a unique position in this debate by criticizing rationalist philosophy in Tahāfut al-Falāsifah and establishing a synthesis between reason and mystical experience in Iḥyā' 'Ulūm al-Dīn and al-Munqidh min al-Ḍalāl. This study aims to analyze how Al-Ghazali formulated Sufism as an epistemological bridge between rationality and spirituality in classical Islam. Using a qualitative approach based on literature study, this study examines Al-Ghazali's main texts and compares them with the thoughts of contemporary philosophers and Sufis. The results show that Al-Ghazali did not reject rationality completely, but positioned reason as a limited instrument that needs to be equipped with spiritual illumination (kashf). This integration allows Sufism to become part of Sunni orthodoxy while providing an epistemological basis for classical Islamic thought. This finding has implications for strengthening the relevance of Sufism in contemporary scientific discourse, especially in developing a paradigm that accommodates both critical reasoning and spiritual awareness in Islamic studies.